On the Economic Consequences of Mass Shootings - Abel Brodeur; Hasin Yousaf (Global Labor Organization (GLO), 2022)
In this paper, we investigate the economic consequences of mass shootings. We find that shootings have negative effects on targeted counties' economies. Estimates using three different comparison groups yield similar results. Examining the mechanisms, we find that residents of targeted areas: (i) develop pessimistic views of financial and local business conditions; and (ii) are more likely to report poor mental health, which hinders usual activities such as work, suggesting that shootings lead to decreases in productivity. Further, we find that greater national media coverage of shootings exacerbates their local economic consequences.
Keywords: D74; L82; C13; I15; D84; 330; Mass Shootings; Employment; Absenteeism; Economic Expectations; Media Coverage